2021
DOI: 10.1021/acsami.1c05950
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Hydrogel Binding Matrix for Dual Signal Amplification in Fluorescence Affinity Biosensors and Peptide Microarrays

Abstract: A combined approach to signal enhancement in fluorescence affinity biosensors and assays is reported. It is based on the compaction of specifically captured target molecules at the sensor surface followed by optical probing with a tightly confined surface plasmon (SP) field. This concept is utilized by using a thermoresponsive hydrogel (HG) binding matrix that is prepared from a terpolymer derived from poly­(N-isopropylacrylamide) (pNIPAAm) and attached to a metallic sensor surface. Epi-illumination fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…This value translates to the swelling ratio change of a flat film of 7.5, which is in the range of the one measured previously for the same type of polymer and cross-linking. 30 It is worth of noting that the simulated LSPR spectra qualitatively agree with the measured ones, but the LSPR wavelengths are red-shifted with respect to the measured ones by about 150 nm. This discrepancy can be ascribed to the over-estimation of Au nanoparticle short- and long-axis lengths D ⊥ and D ∥ due to the convolution of tip geometry of the used AFM tip with the particle geometry.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This value translates to the swelling ratio change of a flat film of 7.5, which is in the range of the one measured previously for the same type of polymer and cross-linking. 30 It is worth of noting that the simulated LSPR spectra qualitatively agree with the measured ones, but the LSPR wavelengths are red-shifted with respect to the measured ones by about 150 nm. This discrepancy can be ascribed to the over-estimation of Au nanoparticle short- and long-axis lengths D ⊥ and D ∥ due to the convolution of tip geometry of the used AFM tip with the particle geometry.…”
Section: Resultssupporting
confidence: 67%
“…By raising temperature above LCST to 40 °C, the thickness decreases by a factor of 4.7 and the refractive index increases to n h = 1.42. 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By studying this effect in more detail, it was observed that the temperature-induced collapse of similar pNIPAAm layers led to a decrease in the swelling ratio Q v by a factor of 4.7, but after its postmodification with IgG this ratio dropped to only 1.6. 167 This work suggests that a possible route to circumvent this problem is using ligands with lower molar mass imposing smaller changes to the thermoresponsive characteristics of the pNIPAAm binding matrix. Fig.…”
Section: Plasmonic (Bio)sensorsmentioning
confidence: 99%
“…The finding opens up possibilities for discovering lectin biomarkers toward various biomedical applications, including cancer diagnosis and therapy. Recently, Hageneder et al developed a responsive hydrogel binding matrix for dual signal amplification in fluorescence affinity biosensors and peptide microarrays by using a terpolymer modified metallic sensor surface [148]. The terpolymer, derived from poly(Nisopropylacrylamide) (pNIPAAm), was arranged in arrays of sensing spots and employed for the specific detection of human IgG antibodies against the Epstein−Barr virus (EBV) in diluted human plasma by using a set of peptide ligands.…”
Section: Polymer Hydrogel-based Microarraymentioning
confidence: 99%